FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU IBADAH SHALAT BERJAMAAH DALAM MASYARAKAT DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU - Wati, Reni Sulistiya; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research is titled "Factors Related with the Behavior of Community Prayers in Tuah Karya Village, Tampan District, Pekanbaru City". This research aims to determine the behavior and characteristics of the community in the implementation of congregational prayer and the factors related to the implementation of congregational prayer in Tuah Karya Village, Tampan District, Pekanbaru City. The method used in this research is quantitative research methods with cross sectional study design. The population in this study were Muslim family heads who were in RW 07 RT 08 and RT in Tuah Karya Village, and a large sample of was 111 family heads. The variables in this study are the level of community awareness, level of community education, community work status, community social status and family support. Data were analyzed by using product momment correlation. Based on the result of the research, the level of public awareness in the implementation of congregational prayers in Tuah Karya Village, Tampan District, Pekanbaru City which is in the "Low" category is 2.8% while those in the "High" category are 49.5%, and factors related to The level of public awareness in the implementation of congregational prayers in sequence, namely family support with an r value of 0.624, the social status of the community with an r value of 0.284, while the community work status with an r value of -0.181 and the level of community education with an r value of -0.015 are not related with the implementation of congregational prayers.Â Keywords: Behavior, Prayers, Community